Management of acute kidney disease as part of routine clinical care in low-resource settings: The International Society of Nephrology Kidney Care Network Project - Evans, Rhys D.R.; Sharma, Sanjib K.; Claure-Del Granado, Rolando; Cullis, Brett; Burdmann, Emmanuel A.; Franca, Fos; Aguiar, Junio; Fredlund, Martyn; Hendricks, Kelly; Iturricha-Caceres, Maria F.; Rai, Mamit; Shah, Bhupendra; et al. (PloS one, 2025)
Acute Kidney Disease (AKD) commonly affects disadvantaged populations in low-resourced areas with poor access to kidney care. Here, barriers to management include a lack of AKD education alongside an inability to measure serum creatinine (SCr) to identify kidney disease. The Kidney Care Network (KCN) is a service improvement initiative which aims to implement a novel strategy for the management of AKD into routine clinical care in low- and low-middle income countries (LLMICs). The strategy includes the development of a scoring system to screen patients for risk of AKD and the use of a device to measure SCr at the point-of-care (POC). This approach is underpinned by dedicated AKD training activities for healthcare workers providing front line clinical care. We report feasibility in the implementation of the KCN approach in adults in 4 LLMICs. Between 2018–2020, 4311 patients at project sites in Bolivia, Brazil, Nepal, and South Africa were deemed at risk of kidney disease and underwent SCr testing, predominantly with the POC device. AKD was identified in 2922 (67.8%) patients. AKD was most commonly due to infections and hypovolemia, and as such was treatable by relatively simple means. Most patients with AKD were treated at the site of patient presentation, including rural primary healthcare facilities, and with early AKD identification the need for kidney replacement therapy was low. In-hospital mortality was only 2.9% and follow-up occurred at 3 months in 1865 (62.3%) patients discharged post AKD diagnosis. Hence, we show the KCN approach is a feasible and effective mechanism for improving AKD management in LLMICs.